Behavioral Intention To Use Flip.Id Oleh Perceived Ease Of Use Melalui Attitude Towards Using - Sri Wulan Handayani; Rayhan Gunaningrat; Agus Suyatno (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
Digital financial services in Indonesia, one of which is Flip which provides interbank transfer services for free and also free of charge. This study wants to know and measure the level of acceptance and understanding in using a Flip e-wallet service through the Technology Acceptance Model (TAM) which is determined by the perception of ease of use through usage attitude as a mediation variable. The data analysis technique used is Structural Equation Modeling (SEM) which uses PLS (Partial Least Square) Software. The characteristics of respondents used in data processing are Surakarta people with age criteria of 19-44 years and frequency of use of Flip <1 month in 2023.The results obtained from the data processing above explain that the perceived ease of use has no effect on the behavioral intention to use. Attitude towards using are able to mediate the influence between perceived ease of use and behavioral intention to use Flip e-wallet service.